Efficiency measurement of Islamic and conventional banks in Saudi Arabia:an empirical and comparative analysis - Nauman Khan, Muhammad; Amin, Md Fouad; Khokhar, Imran; Hassan, Mehboob ul; Ahmad, Khaliq (IIUM Press, International Islamic University Malaysia, 2018)
Saudi Arabia, beside Malaysia and many other Muslim countries, is one of those countries where Islamic and conventional banking operate in parallel. Over the last decade, the country’s banking industry is growing at rapid pace that accounts for the largest share in GCC. The present study measures and compares the performance of Saudi conventional and Islamic banking industry and identifies the areas where the strategic measures are required to improve the banking performance. It applies non-parametric Data Envelopment Analysis (DEA) for the data from 2008-2016 of Saudi banking industry and provides comprehensive empirical results at individual bank vis-a-vis industry levels. The empirical results demonstrate a mix trend among the banks in achieving technical, pure technical and scale efficiency. It is observed that with the common pledge to expanding market share and performance, both conventional and Islamic banks have been successful in improving their levels of efficiency. At individual bank level, Al-Rajhi is the only bank that has achieved the highest score in terms of technical, pure technical and scale efficiency, while in the conventional banking group, both Saudi Hollandi and National Commercial banks are found on the top position. Despite the growth of incomes and deposits of entire banking industry in Saudi Arabia, this study particularly recommends for the Islamic banks to redirect their short term and long-term marketing strategies and to focus on improving their management skills at the branch level.